2022
DOI: 10.1007/s12072-022-10312-z
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation in alcohol-associated acute-on-chronic liver failure: an open-label clinical trial

Abstract: Background: Severe alcoholic hepatitis (SAH) presenting as acute-on-chronic liver failure (ACLF) carries a high short-term mortality. Alteration of gut microbiota is a crucial component implicated in its pathogenesis, whose modulation has been suggested as a potential therapeutic tool. We evaluated the safety of fecal microbiota transplantation (FMT) and its e cacy in improving short-term survival and clinical severity scores in patients with SAH-ACLF. Methods: Thirty-three patients [13 in the FMT arm;20 in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…The survival rates in ACLF patients with higher grades at the end of 548 days was 58.3%, demonstrating proof of concept on the benefits of FMT in this very sick group with SAH-related ACLF [ 18 ]. Similarly, a recent study from India by researchers at the Post Graduate Institute, Chandigarh also validated findings that FMT was safe, improved short-term and medium-term survival, and led to improvement in clinical severity scores in patients [ 19 ]. Bajaj et al .…”
Section: Discussionmentioning
confidence: 63%
“…The survival rates in ACLF patients with higher grades at the end of 548 days was 58.3%, demonstrating proof of concept on the benefits of FMT in this very sick group with SAH-related ACLF [ 18 ]. Similarly, a recent study from India by researchers at the Post Graduate Institute, Chandigarh also validated findings that FMT was safe, improved short-term and medium-term survival, and led to improvement in clinical severity scores in patients [ 19 ]. Bajaj et al .…”
Section: Discussionmentioning
confidence: 63%
“…Ascites was improved and plasma IL-1b was reduced in the FMT group. [68] This article is protected by copyright. All rights reserved.…”
Section: Impact Of Fmt On Alcohol-associated Hepatitismentioning
confidence: 99%
“…Fecal microbiota transplantation (FMT), which involves the transfer of donor stool into recipients, is increasingly being explored as a potential treatment in gastric intestinal and liver diseases [191]. Clinical trials supported the safety of FMT and have shown improvement of survival and clinical severity in patients with severe alcoholic hepatitis [192,193]. However, FMT can be lethal for elderly people because of serious compli-cations, such as infections from multidrug-resistant organisms [194].…”
Section: Microbiological Therapymentioning
confidence: 99%